1999
DOI: 10.1128/mcb.19.12.8281
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Portable Repression Domain and an E1A-Responsive Activation Domain in Pax4: a Possible Role of Pax4 as a Transcriptional Repressor in the Pancreas

Abstract: Pax4 is a paired-domain (PD)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
1
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 61 publications
2
62
1
2
Order By: Relevance
“…The Cterminal domain missing in ilr3-1 does not contain recognizable motifs, but is conserved in other members of the ILR3 bHLH subgroup (Heim et al 2003), including those in rice (Figure 2A). Other bHLH proteins have similarly positioned transcriptional activation (Franks and Crews 1994;Gerber et al 1997;Ema et al 1999) or repression domains (Sato et al 1994;Fisher et al 1996;Fujitani et al 1999). As the bHLH and leucine zipper domains remain intact in ilr3-1, it is tempting to speculate that the ilr3-1 protein still dimerizes and binds DNA via the intact bHLH and leucine zipper domains, but the missing C-terminal domain prevents proper modulation of gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…The Cterminal domain missing in ilr3-1 does not contain recognizable motifs, but is conserved in other members of the ILR3 bHLH subgroup (Heim et al 2003), including those in rice (Figure 2A). Other bHLH proteins have similarly positioned transcriptional activation (Franks and Crews 1994;Gerber et al 1997;Ema et al 1999) or repression domains (Sato et al 1994;Fisher et al 1996;Fujitani et al 1999). As the bHLH and leucine zipper domains remain intact in ilr3-1, it is tempting to speculate that the ilr3-1 protein still dimerizes and binds DNA via the intact bHLH and leucine zipper domains, but the missing C-terminal domain prevents proper modulation of gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Its relative activity is, however, more than twofold lower than Pax-6 TAD and inactive in pancreatic islet-cell lines [23,37]. Moreover, repression domains have been mapped to the Pax-4 HD and C-terminal region [22,23,27] but no cofactors mediating this effect have as yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Pax-4 has been shown to act as a DNA binding dependent transcriptional repressor in a Gal4 system [22,23] and inhibits several islet specific promoters such as the glucagon, insulin and islet amyloid polypeptide (IAPP), and its own promoter in transient transfection studies [22, 24±27]. Pax-4 might therefore be implicated in a-cell-specific expression of the glucagon gene by suppressing glucagon gene transcription in differentiating insulin-producing cells.…”
mentioning
confidence: 99%
“…In contrast to many target genes of Pa 6, the target genes of Pa 4 have not yet been found in spite of an extensive search. Recently, it was reported that DNA binding specificities of Pa 4 and Pa 6 are similar and Pa 4 can act as a Pa 6 repressor by the competition for binding sites [25,26]. Possibly Pa 4 inhibits the induction of the alpha-cell phenotype by Pa 6 in normal beta cells.…”
Section: Discussionmentioning
confidence: 99%